Efficacy of Cognitive Behavioral Therapy on Mood Disorders, Sleep, Fatigue, and Quality of Life in Parkinson's Disease: A Systematic Review and Meta-Analysis - Luo, Fangyi; Ye, Mengfei; Lv, Tingting; Hu, Baiqi; Chen, Jiaqi; Yan, Junwei; Wang, Anzhe; Chen, Feng; He, Ziyi; Ding, Zhinan; Zhang, Jian; Qian, Chao; et al. (Frontiers in Psychiatry, 2021)
Objective: The aim of this study was to perform a quantitative analysis to evaluate the efficacy of cognitive behavioral therapy (CBT) on mood disorders, sleep, fatigue, and its impact on quality of life (QOL) in Parkinson's Disease (PD). Methods: We searched for randomized controlled trials in three electronic databases. Fourteen studies, including 507 patients with PD, met the inclusion criteria. We determined the pooled efficacy by standard mean differences and 95% confidence intervals, using I2 to reveal heterogeneity. Results: The result showed CBT had a significant effect on depression [−0.93 (95%CI, −1.19 to −0.67, P < 0.001)] and anxiety [−0.76 (95%CI, −0.97 to −0.55, P < 0.001)]. Moderate effect sizes were noted with sleep disorders [−0.45 (95% CI, −0.70 to −0.20, P = 0.0004)]. There was no evident impact of CBT on fatigue or QOL. We found an intervention period >8 weeks was advantageous compared with <8 weeks, and CBT implemented in non-group was more effective than in group. Between the delivery methods, no significant difference was found. Conclusion: We found that CBT in patients with PD was an efficacious therapy for some non-motor symptoms in PD, but not efficacious for fatigue and QOL. These results suggest that CBT results in significant improvement in PD and should be used as a conventional clinical intervention.